Reduced Susceptibility to Fluoroquinolone in Salmonella typhi and Some Molecular Characteristics of Fluoroquinolone Resistance in Indigenous Isolates - Mahmud, Abu Sayeed M; Mahmud, M Nuruddin; Hakim, M Abdul (Bangladesh Journal of Microbiology, 2011)
Typhoid fever and Salmonella typhi bacteremia among the patients were evaluated at Dhaka Shishu Hospital, Popular Diagnostic Center, Kumudiny Hospital and other sites throughout Bangladesh. Among the 943 Salmonella typhi isolates studied, 57.4% showed resistance to ampicillin (MIC > 256 mg/ml), 58 % to cotrimoxazole (MIC > 32 mg/ ml) and 58.6% to chloramphenicol (MIC > 256 mg/ml). Significant resistance (97.8%) was observed against first generation quinolone, nalidixic acid (MIC > 256 mg/ml) whereas only 11 isolates (1.1%) were resistant to second generation fluoroquinolone, ciprofloxacin. Among 943 isolates E-strip test of 411 isolates for ciprofloxacin showed that 53 isolates were very sensitive (MIC < 0.125 mg/ml), 252 were sensitive (MIC between 0.125 mg/ ml and 0.5 mg/ ml), 95 were moderately sensitive (MIC between 0.5 mg/ml and 2.0 mg/ml) and the rest were resistant (MIC >2.0 ìg/ml) or very highly resistant (MIC 512 mg/ml). However, all isolates including ciprofloxacin resistant S. typhi were found sensitive to a third generation cephalosporin ceftazidime. All the isolates resistant to ciprofloxacin were found to be identical by API 20 E (Analytical Profile Index) score (4404552) and VNTR typing. Digestion of PCR product (195 bp gyrase A) of ciprofloxacin resistant strain with Hind l did not make any change, compared to the undigested product of the same strains in the electrophoresis banding pattern, indicating the presence of mutations at both the ser-83 and asp-87 sites of the genome Gyr A. In contrast, the PCR product from nalidixic acid susceptible control strain cleaved at both sites, ser-83 and asp-87. Key words: VNTR; Antibiotic resistance; Quinolone; Salmonella DOI: http://dx.doi.org/10.3329/bjm.v27i2.9169 BJM 2010; 27(2): 38-41